Modelling shape and parameterising style: an approach to the design of high-fashion shoe lasts. (2nd September 2022) - Chertenko, Liliia; Booth, Brian G.
Abstract: A shoe's shape, captured by the shoe last, is designed based on the anatomical parameters of the foot. However, changing footwear fashions result in a variety of shapes and styles of last, which complicates the determination of ergonomic shoe forms. We propose a method for simple customisation of a shoe's style while retaining an ergonomic fit. 3D foot scans were used initialise the design of a shoe last based on the average foot shape of the target population. The shoe styles are then modelled as changes to the toe box, which is style dependent and thus, free to model, and the height of the heel lift, which is based on 3D geometric calculations linked to the anthropometric parameters of the foot. The proposed method was tested using consumer surveys. The results of the surveys showed an increase in comfort and satisfaction compared to shoe samples made with standard commercial lasts.